2005
DOI: 10.1159/000085581
|View full text |Cite
|
Sign up to set email alerts
|

Trichoscan: What Is New?

Abstract: The treatment of androgenetic alopecia (AGA) is usually long lasting, and the effects of treatment attempts are difficult to measure. Consequently, there was a need for a sensitive tool to monitor hair loss and treatment response. Therefore, we developed the Trichoscan as a method which combines epiluminescence microscopy with automatic digital image analysis for the measurement of human hair. The Trichoscan is able to analyze all important parameters of hair growth (density, diameter, growth rate, vellus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
0
18
1
2
Order By: Relevance
“…[41] Thus, the TrichoScan method provides a reliable before-and-after comparison and is highly reproducible during the course of a clinical study. [404146] The increase in the measured hair count from 123 hairs/cm 2 at baseline to 159 and 173 hairs/cm 2 after 3 and 6 months, respectively, must be considered clinically relevant. Study 4 was conducted as an observational study including 60 patients, in which significant improvements were identified in the before-and-after comparisons of hair texture and hair loss; however, the study included no placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…[41] Thus, the TrichoScan method provides a reliable before-and-after comparison and is highly reproducible during the course of a clinical study. [404146] The increase in the measured hair count from 123 hairs/cm 2 at baseline to 159 and 173 hairs/cm 2 after 3 and 6 months, respectively, must be considered clinically relevant. Study 4 was conducted as an observational study including 60 patients, in which significant improvements were identified in the before-and-after comparisons of hair texture and hair loss; however, the study included no placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…The sites are cleaned with an alcoholic solution and photographed again. The technique is easy to perform, highly validated, [19][20][21] noninvasive, and with the exception of the tattoo marking the site, causes no discomfort to the patient. 22 Measurements were performed on day 1 (hair diameter) and day 4 (hair density and anagen/telogen ratio) of each assessment period.…”
Section: Evaluationsmentioning
confidence: 99%
“…TrichoScan Ò Research (TRICHOLOG GmbH, Freiburg, Germany), for example, has many built-in features, including the automatic analysis of the hair condition, hair count, hair thickness, and hair length. [20][21][22][23] The method uses an image processing technique to quantify hair. 24 However, the analysis area is up to a 2 cm 2 circle, and the test requires the application of hair dye.…”
Section: Introductionmentioning
confidence: 99%